2018
DOI: 10.1159/000486684
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Therapy as Adjuvant Treatment for Hardware-Related Infections in Neuromodulation

Abstract: Background: In neuromodulation therapies, hardware-related infections are a major challenge often leading to hardware removal. Objective: To investigate the role of adjuvant hyperbaric oxygen therapy (HBOT) in hardware-related infections. Methods: Fourteen hardware-related infection events in 12 consecutive patients between 2002 and 2015 were treated with antibiotics and adjuvant HBOT at the Karolinska University Hospital (Stockholm, Sweden). Two time-independent infection events related to hardware replacemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…HBOT has been used for decades as an effective treatment in complicated infectious disease cases, by facilitating macrophage and neutrophil killing capacity in hypoxic environments such as abscesses, 17,18 and is known to potentiate the effect of some antibiotics 19 . At our institution, we have positive recent clinical experience with treating both intracranial abscesses and infected intracerebral implants with HBOT 9,11 8,9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBOT has been used for decades as an effective treatment in complicated infectious disease cases, by facilitating macrophage and neutrophil killing capacity in hypoxic environments such as abscesses, 17,18 and is known to potentiate the effect of some antibiotics 19 . At our institution, we have positive recent clinical experience with treating both intracranial abscesses and infected intracerebral implants with HBOT 9,11 8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…A surgical intervention to drain the patient's multiple intracranial abscesses was deemed futile as: (1) diagnosis was already known and relevant antibiotic treatment initiated, and (2) the multiple abscesses were small in nature, without the possibility of significant volumetric reduction by drainage. Instead, based on previous experience 9,11 HBOT was suggested as a treatment adjunct, but not initiated since the patient showed slow improvement with reduced C‐reactive protein over the following 5 days. Nevertheless, no radiological decrease in the abscess formation was seen on an MRI performed at day 6.…”
Section: Case Presentationmentioning
confidence: 99%
“…Moreover, Bartek Jr. et al applied HBOT as adjuvant treatment for hardware-related infections in neuromodulation. The findings of these studies indicated a potential benefit of adjuvant HBOT in the treatment of hardware-related infections in neuromodulation, diminishing the need for hardware removal and treatment interruption [63].…”
Section: Application Of Hbot In Ssis Following Neuromodulation or Neu...mentioning
confidence: 94%
“…Limited O 2 -supply in bacterial biofilms has been demonstrated in several infections, such as necrotizing soft-tissue infections (NSTI; Siemens et al 2016 ), cerebral abscesses, certain implant-related cerebral infections, refractory osteomyelitis, chronic ischemic ulcers, and pulmonary lung infections (Bartek et al 2018 , Moon 2019 ). Therefore, bacteria are subject to a hypoxic or even anoxic microenvironment affecting their sensitivity to certain types of antibiotics intended for infection control (Sønderholm et al 2017 , Jensen et al 2019b ).…”
Section: Treatment Of Biofilms Based On Microenvironmental Characteri...mentioning
confidence: 99%
“…The addition of extra O 2 by hyperbaric oxygen treatment (HBOT) can significantly enhance the efficacy of antibiotic treatment in vitro (Mader et al 1980 , Lima et al 2015 , Kolpen et al 2016 ) and has been shown to enhance antibiotic activity during experimental in vivo biofilm infections (Stewart et al 1999 , Kolpen et al 2016 , Özkan et al 2016 ). Biofilm infections that may become susceptible to antibiotics through the use of oxygenation include endocarditis (Özkan et al 2016 , Lerche et al 2017 ), osteomyelitis (Yu et al 2011 ), brain abscesses (Bartek et al 2016 , Kutlay et al 2005 ), and device-related infections (Bartek et al 2018 ). However, the clinical effects of HBOT treatment on infections are mainly available from pro and retrospective case-control studies (Thom 2011 ), whereas randomized, controlled trials are still lacking.…”
Section: Treatment Of Biofilms Based On Microenvironmental Characteri...mentioning
confidence: 99%